Registration of visual impairment due to diabetic retinopathy in a subpopulation of Cambridgeshire - Patel Gordon-Bennett (Dove Medical Press, 2008)
Patel Gordon-Bennett1, Aseema Misra2, Wendy Newsom1, Declan Flanagan21Eye Department, Hinchingbrooke Hospital, Hinchingbrooke Park, Huntingdon, Cambridgeshire, UK; 2Eye Department, Addenbrookes Hospital, Hills Road, Cambridge, Cambridgeshire, UKBackground/Aims: The UK National Screening Committee (NSC) has set 18 standards for diabetic retinopathy (DR) screening services in England and Wales, the first of which is to reduce new visual impairment (VI) due to DR by 10% within 5 years. This study examined the incidence of VI due to DR in Cambridgeshire (City, South, and Huntingdonshire) in order to establish a baseline rate of VI registration.Methods: A retrospective review of all certificates of visual impairment (CVI) for 2004 and 2005 was conducted. Hospital records of patients registered due to DR were reviewed to ascertain conformity to NSC Standards. The incidence of VI registration due to DR was calculated.Results: The number of registrations predominantly due to DR was 18; 13 visually impaired and 5 with severe VI. The rates of VI and severe VI predominantly due to DR were 17.1 and 6.5 per million per year, respectively. The VI and severe VI registration rates in the diabetic population were 600 and 230 per million per year, respectively.Conclusion: The severe VI registration rate due to DR lies within the national standard. The VI registration rate exceeds 1990–1991 national standards but lies within 1999–2000 national figures.Keywords: diabetic retinopathy, visual impairment, severe visual impairment, registration, certification of visual impairment